Can Game-Based Learning Help to Increase the Awareness of Water Management in Uganda? A Case Study for Primary and Secondary Schools - Brian Nalumenya; Matteo Rubinato; Michael Kennedy; Jade Catterson (World)
In the Ugandan curriculum, theoretical teaching predominates in conveying water-related topics due to its efficiency and low resource requirements. However, this teacher-centred approach limits student interaction and collaborative learning. Conversely, game-based learning can enhance social skills, critical thinking, and engagement, yet it remains underutilised in Ugandan education. To address this gap, this study developed three educational games: Water Conservation Snakes and Ladders (WCSL), Water Awareness Quartet Cards (WAQC), and Water Pollution Puzzle (WPP). These games were implemented in four schools—three primary and one secondary—where students engaged in competitive, team-based play. The impact of these games on learning outcomes was assessed through pre- and post-test questionnaires. Descriptive and thematic analysis indicated a significant positive effect, with WAQC showing a 25% greater influence on performance than WCSL (18%) and WPP (14%). The findings also underscored the importance of age in determining game acceptability and enjoyment. To enhance education on water-related issues, it is recommended that these topics be integrated into both Science and Social Studies curricula and taught consistently across academic terms. Ultimately, the Ugandan government should consider incorporating game-based learning strategies into schools to improve student engagement and learning in water resource management.